Investigating in vivo airway wall mechanics during tidal breathing with optical coherence tomography - Robertson, Claire (Society of Photo-Optical Instrumentation Engineers (SPIE), 2011)
Optical coherence tomography (OCT) is a nondestructive imaging technique offering high temporal and spatial resolution, which makes it a natural choice for assessing tissue mechanical properties. We have developed methods to mechanically analyze the compliance of the rabbit trachea in vivo using tissue deformations induced by tidal breathing, offering a unique tool to assess the behavior of the airways during their normal function. Four-hundred images were acquired during tidal breathing with a custom-built endoscopic OCT system. The surface of the tissue was extracted from a set of these images via image processing algorithms, filtered with a bandpass filter set at respiration frequency to remove cardiac and probe motion, and compared to ventilatory pressure to calculate wall compliance. These algorithms were tested on elastic phantoms to establish reliability and reproducibility. The mean tracheal wall compliance (in five animals) was 1.3±0.3×10(−5) (mm Pa)(−1). Unlike previous work evaluating airway mechanics, this new method is applicable in vivo, noncontact, and loads the trachea in a physiological manner. The technique may have applications in assessing airway mechanics in diseases such as asthma that are characterized by significant airway remodeling.